Polydopamine / nano-silver spherical antibacterial powder coating as well as preparation method and application thereof
By using barriers and acid etching in antibacterial powder coatings to form spherical powders, and using dopamine self-polymerization and silver ion reduction to construct polydopamine/nanosilver spherical structures, the problem of nanosilver aggregation and poor interface interactions is solved. It improves the fluidity and antibacterial properties of antibacterial powder coatings, and achieves efficient antibacterial effects.
Patent Information
- Application Number
- CN202411574762.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-06
AI Technical Summary
During the preparation process of existing antibacterial powder coatings, the orange peel phenomenon caused by nanosilver agglomeration, poor interface interaction between nanosilver and matrix, and insufficient fluidity, affects the appearance and performance of the coating.
By mixing the resin powder with a barrier and stirring in a microwave oven, a spherical powder is formed, and a nanopore structure is formed by acid etching. The self-polymerization of dopamine forms active sites in the nanopores, and then in situ reduction of silver ions is carried out through the silver ions. Construct polydopamine/nano-silver spherical antibacterial powder coating to improve fluidity and antibacterial properties.
It effectively improves the fluidity, coating performance and antibacterial properties of antibacterial powder coatings, has good fluidity and an antibacterial rate of up to 99.9%, solving the problems of nano-silver aggregation and poor interface interaction.
Smart Images

Figure CN119242166A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of antibacterial powder coatings and relates to a polydopamine / nano-silver spherical antibacterial powder coating and a preparation method and application thereof. Background Art
[0002] As people's health awareness increases, antimicrobial coatings, as a new type of material with antimicrobial properties, have received more and more attention. Antimicrobial coatings have a wide range of applications, such as medical institutions, schools, offices, furniture and public transportation. However, as countries continue to issue restrictions on volatile organic compounds (VOCs), strict requirements and prevention and control technical measures have been formulated for the emission of VOCs during the coating process. Compared with traditional liquid coatings, antimicrobial powder coatings, as a coating variety with high production efficiency, excellent coating performance, eco-friendly and economical, have the inherent advantage of preventing and controlling VOCs, and its recovery rate can reach 98%.
[0003] Antibacterial powder coating is a special type of powder coating developed in recent years. Among them, nanosilver is a highly efficient and broad-spectrum inorganic antibacterial agent with many advantages such as long-lasting antibacterial performance, high safety, strong antibacterial effect, and not easy to produce drug resistance. Powder coatings with nanosilver as antibacterial additives not only have the inherent advantages of powder coatings, but also have surface antibacterial properties, which play a positive role in reducing the spread of pathogens and have broad application prospects. However, due to the large specific surface area, nanosilver has a certain degree of agglomeration, and the lack of active groups on the surface of nanosilver makes it difficult to effectively combine with the coating matrix. At the same time, the poor fluidity of conventional powder coatings will lead to uneven distribution during the spraying process, resulting in bubbles and orange peel phenomenon in the coating, which ultimately affects the appearance and performance of the coating. Therefore, finding an appropriate method to introduce nanosilver particles into the powder coating matrix and solve the fluidity of powder coatings is an urgent problem to be solved. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of nanosilver agglomeration, poor interface interaction between nanosilver and substrate, orange peel phenomenon caused by insufficient fluidity of antibacterial coating, etc. in the prior art when preparing antibacterial powder coating, thereby providing a method for preparing polydopamine / nanosilver spherical antibacterial powder coating, which can prepare spherical powder coating by the action of barrier agent, then form nanopore structure in situ under acid etching, form active sites in situ in nanopores by self-polymerization of dopamine, and finally construct polydopamine / nanosilver spherical antibacterial powder coating by in situ reduction of silver ions. Spherical powder coating can effectively improve the fluidity of powder coating, the loading of polydopamine can be used as a "bridge" to strengthen the combination of coating substrate and nanosilver, and the active group of polydopamine can complex silver ions, which is conducive to reducing the agglomeration of nanosilver, thereby effectively improving the fluidity, coating performance and antibacterial performance of antibacterial powder coating.
[0005] In order to solve the above technical problems, the present invention is implemented through the following technical solutions.
[0006] The present invention provides a method for preparing a polydopamine / nanosilver spherical antibacterial powder coating, comprising the following steps:
[0007] (1) The resin powder coating matrix and the barrier agent are mixed evenly and placed in a microwave oven, and stirred at an output power of 500-1000 W; then, water and an etchant are added and stirred for 6-24 hours; after the reaction is completed, an alkaline solution is added and the reaction is continued for 6-24 hours, and then washed and dried to obtain a spherical resin powder with a nanoporous structure;
[0008] (2) placing the spherical resin powder with a nanoporous structure obtained in step (1) in a container, adding water and tris(hydroxymethyl)aminomethane, and adjusting the pH to 8-9 using a pH adjuster; then adding dopamine hydrochloride and stirring to react to obtain a polydopamine functionalized spherical powder;
[0009] (3) The polydopamine functionalized spherical powder is washed and placed in a container together with water, and a silver nitrate solution is slowly added for stirring reaction; then a reducing agent is slowly added for heating and stirring reaction, and then washed and dried to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0010] Preferably, the resin powder coating matrix in step (1) is selected from one or more of triglycidyl isocyanurate (TGIC), polyester resin, epoxy resin E12, polyurethane resin (PU), polyamide resin (PA), polyethylene resin (PE), and fluorocarbon resin (PVDF).
[0011] Preferably, the barrier agent in step (1) is selected from one or more of fumed nano-silicon dioxide, fumed nano-silicon dioxide, nano-zinc oxide, nano-ferroferric oxide, and nano-aluminum oxide.
[0012] Preferably, the etchant in step (1) is selected from one or more of HCl, HF, LiF, and H2SO4.
[0013] Preferably, the alkaline solution in step (1) is selected from one or more of NaOH solution, KOH solution, NaHCO3 solution, and Na2CO3 solution.
[0014] Preferably, the molar ratio of the etchant to the barrier agent in step (1) is 1:1-4.
[0015] Preferably, in step (1), the molar ratio of the etchant to the solute in the alkaline solution is 1:1-5.
[0016] Preferably, in step (1), the output power of the microwave oven is 600-900 W, and the stirring time is 80-150 s; more preferably, the output power of the microwave oven is 700 W, and the stirring time is 110-130 s.
[0017] Preferably, in step (1), water and an etchant are added and stirred to react for 9-18 hours; more preferably, water and an etchant are added and stirred to react for 12 hours.
[0018] Preferably, in step (1), the alkaline solution is added and the reaction is continued for 9-18 hours; more preferably, the alkaline solution is added and the reaction is continued for 12 hours.
[0019] Preferably, the washing in step (1) is performed by washing with water; more preferably, the washing is performed by washing with deionized water for 1-6 times; most preferably, the washing is performed by washing with deionized water for 4 times.
[0020] Preferably, the drying temperature in step (1) is 30-60°C and the drying time is 12-72h; more preferably, the drying temperature is 35-50°C and the drying time is 24-54h; most preferably, the drying temperature is 40°C and the drying time is 48h.
[0021] Preferably, the pH adjuster in step (2) is selected from one or more of hydrochloric acid, nitric acid, sulfuric acid and acetic acid.
[0022] Preferably, the stirring reaction in step (2) is carried out at a temperature of 18-30°C for a time of 12-48 hours; more preferably, the stirring reaction is carried out at a temperature of 20-25°C for a time of 18-30 hours.
[0023] Preferably, in step (2), the mass ratio of the spherical resin powder with nanoporous structure to dopamine hydrochloride is 0.2-5:1; more preferably, the mass ratio of the spherical resin powder with nanoporous structure to dopamine hydrochloride is 0.5-3:1.
[0024] Preferably, in step (3), the polydopamine functionalized spherical powder is washed under reduced pressure with deionized water; more preferably, the polydopamine functionalized spherical powder is washed under reduced pressure with deionized water for 1-6 times; most preferably, the polydopamine functionalized spherical powder is washed under reduced pressure with deionized water for 3 times.
[0025] Preferably, in step (3), the mass ratio of the polydopamine functionalized spherical powder to silver nitrate is 1-20:1; more preferably, the mass ratio of the polydopamine functionalized spherical powder to silver nitrate is 4-16:1.
[0026] Preferably, the reducing agent in step (3) is selected from one or more of DMF, glucose, ascorbic acid and NaBH4.
[0027] Preferably, in step (3), the molar ratio of the reducing agent to Ag in the silver nitrate solution is 1:0.5-2; more preferably, the molar ratio of the reducing agent to Ag in the silver nitrate solution is 1:1.
[0028] Preferably, the stirring reaction in step (3) is carried out at a temperature of 18-30°C for 2-12 hours; more preferably, the stirring reaction is carried out at a temperature of 20-25°C for 4-8 hours.
[0029] Preferably, the temperature of the heating and stirring reaction in step (3) is 40-60°C, and the time is 1-7h; more preferably, the temperature of the heating and stirring reaction is 45-55°C, and the time is 3-5h.
[0030] Preferably, the washing in step (3) is performed using water; more preferably, the washing is performed using deionized water for 1-6 times; most preferably, the washing is performed using deionized water for 4 times.
[0031] Preferably, the drying temperature in step (3) is 30-60°C and the drying time is 12-72h; more preferably, the drying temperature is 35-50°C and the drying time is 24-54h; most preferably, the drying temperature is 40°C and the drying time is 48h.
[0032] The second aspect of the present invention provides a polydopamine / nanosilver spherical antibacterial powder coating prepared according to the above preparation method.
[0033] The third aspect of the present invention provides an antibacterial powder coating, comprising the polydopamine / nanosilver spherical antibacterial powder coating prepared according to the above preparation method.
[0034] Preferably, the antibacterial powder coating is prepared by the following method: spraying polydopamine / nanosilver spherical antibacterial powder coating to form a coating, followed by curing, heating and melting and leveling.
[0035] Preferably, the spraying is electrostatic spraying.
[0036] Preferably, the coating has a thickness of 70-100 μm.
[0037] Preferably, the curing heating treatment is performed at a temperature of 170-200° C. and a time of 5-20 min.
[0038] Compared with the existing technology, the present invention has the following beneficial effects:
[0039] (1) The present invention prepares spherical powder by treating resin powder with a barrier agent, and then treating with an etchant to remove the barrier agent, thereby forming a porous structure on the surface of the polyamide. On the one hand, the spherical structure can greatly improve the fluidity of the powder and avoid the orange peel phenomenon caused by insufficient fluidity of the antibacterial powder; on the other hand, the formation of the porous structure is conducive to the subsequent loading of silver, improving the interface interaction between nanosilver and the powder matrix, while avoiding reducing the agglomeration of silver.
[0040] (2) The polydopamine loading used in the present invention can be used as a "bridge" to strengthen the combination of the powder matrix and nanosilver. At the same time, the active groups of polydopamine can complex silver ions, which is beneficial to reduce the agglomeration of nanosilver, thereby effectively improving the fluidity, coating performance and antibacterial performance of the antibacterial powder coating.
[0041] (3) The antibacterial powder coating prepared by the present invention has good fluidity, stable performance, and an antibacterial rate of more than 99.9%. It can be directly used as an antibacterial agent in various types of scenarios, and can also be further processed according to actual needs, such as coating to form an antibacterial coating for use. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The figure is a schematic diagram of the reaction flow of microwave spheroidization of the present invention.
[0043] Figure 2 This is the SEM morphology of the polyamide powder obtained before and after treatment with the barrier agent and the etchant in Example 1 of the present invention.
[0044] Figure 3 This is the XRD pattern of Ag@PDA@PA prepared in Example 1 of the present invention.
[0045] Figure 4 It is the board surface diagram of Example 1 and Comparative Examples 2-4 of the present invention.
[0046] Figure 5 The anti-E. coli effect diagram of the antibacterial coating of Example 1 and Comparative Example 4 of the present invention after culturing for 1h and 6h.
[0047] Figure 6 This is a diagram showing the anti-Escherichia coli effect of the antibacterial coating of Example 1 and Comparative Examples 1 and 4 of the present invention after 6 hours of culture. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0049] Unless otherwise defined, all technical terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.
[0050] Example 1
[0051] A polydopamine / nanosilver spherical antibacterial powder coating, the spherical reaction process is as follows Figure 1 As shown, the preparation method comprises the following steps:
[0052] (1) 120 g of polyamide PA powder and 30 g of fumed nano-silica R972 were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotary drum, and stirred for 110 s at an output power of 700 W; then, 600 mL of deionized water and 40% hydrofluoric acid solution were added and stirred for 12 h, wherein the molar ratio of HF to fumed nano-silica was 1.5:1; after the reaction was completed, 5 M NaOH solution was slowly added and the reaction was continued for 12 h, wherein the molar ratio of HF to NaOH was 1:2.5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain a spherical polyamide powder with a nanoporous structure.
[0053] (2) 50 g of the spherical polyamide powder with a nanoporous structure obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.6 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.2 with 0.5 M HCl; then 25 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a spherical polyamide powder functionalized with polydopamine.
[0054] (3) The polydopamine functionalized spherical polyamide powder was washed with deionized water under reduced pressure for three times and then placed in a 1000-mL beaker together with 400 mL of deionized water. A 2 g / L silver nitrate solution was slowly added and stirred at room temperature for 6 hours, wherein the mass ratio of the polydopamine functionalized spherical polyamide powder to AgNO3 was 8:1. Subsequently, DMF was slowly added and heated and stirred at 50°C for 4 hours, wherein the molar ratio of AgNO3 to DMF in the AgNO3 solution was 1:1. The powder was then washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0055] Furthermore, the polydopamine / nanosilver spherical antibacterial powder coating prepared above was electrostatically sprayed on a tinplate to form a coating with a thickness of 100 μm, and then heat-treated at 170° C. for 10 min to melt and level the coating, thereby obtaining an antibacterial powder coating.
[0056] Example 2
[0057] A polydopamine / nanosilver spherical antibacterial powder coating, the preparation method of which comprises the following steps:
[0058] (1) 116.67 g of polyester resin / TGIC mixture (wherein the mass ratio of polyester resin to TGIC is 96:4) and 33.33 g of nano-ferroferric oxide were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotary drum, and stirred for 120 s at an output power of 700 W; then, 600 mL of deionized water and 40% hydrochloric acid solution were added and stirred for 12 h, wherein the molar ratio of HCl to nano-ferroferric oxide was 1.5:1; after the reaction was completed, 5 M NaOH solution was slowly added and the reaction was continued for 12 h, wherein the molar ratio of HCl to NaOH was 1:2.5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain spherical polyester TGIC powder with a nanoporous structure.
[0059] (2) 50 g of the spherical polyester TGIC powder with a nanoporous structure obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.65 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.4 with 0.75 M HCl; then 50 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a spherical polyester TGIC powder functionalized with polydopamine.
[0060] (3) The polydopamine functionalized spherical polyester TGIC powder was washed with deionized water under reduced pressure for three times and then placed in a 1000-mL beaker together with 400 mL of deionized water. 1.5 g / L of silver nitrate solution was slowly added and stirred at room temperature for 5 hours, wherein the mass ratio of the polydopamine functionalized spherical polyester TGIC powder to AgNO3 was 8:2; glucose was then slowly added and heated and stirred at 50°C for 4.5 hours, wherein the molar ratio of AgNO3 to glucose in the AgNO3 solution was 1:1; the powder was then washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0061] Furthermore, the polydopamine / nanosilver spherical antibacterial powder coating prepared above was electrostatically sprayed on a tinplate to form a coating with a thickness of 75 μm, and then heat-treated at 180° C. for 15 min to melt and level the coating, thereby obtaining an antibacterial powder coating.
[0062] Example 3
[0063] A polydopamine / nanosilver spherical antibacterial powder coating, the preparation method of which comprises the following steps:
[0064] (1) 112.5 g of polyurethane PU powder and 37.5 g of nano-alumina were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotating drum, and stirred for 130 s at an output power of 700 W; then, 600 mL of deionized water and 40% dilute sulfuric acid solution were added and stirred for 12 h, wherein the molar ratio of H2SO4 to nano-alumina was 1.5:2; after the reaction was completed, 5 M NaOH solution was slowly added and the reaction was continued for 12 h, wherein the molar ratio of H2SO4 to NaOH was 1:5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain a spherical polyurethane powder with a nanoporous structure.
[0065] (2) 50 g of the spherical polyurethane powder with a nanoporous structure obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.7 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.5 with 1 M HCl; then 100 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a spherical polyurethane powder functionalized with polydopamine.
[0066] (3) The polydopamine functionalized spherical polyurethane powder was washed with deionized water under reduced pressure for three times and then placed in a 1000-mL beaker together with 400 mL of deionized water. A 3 g / L silver nitrate solution was slowly added and stirred at room temperature for 5.5 hours, wherein the mass ratio of the polydopamine functionalized spherical polyurethane powder to AgNO3 was 9:1. Subsequently, ascorbic acid was slowly added and heated and stirred at 50°C for 4 hours, wherein the molar ratio of AgNO3 to ascorbic acid in the AgNO3 solution was 1:1. The powder was then washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0067] Furthermore, the polydopamine / nanosilver spherical antibacterial powder coating prepared above was electrostatically sprayed on a tinplate to form a coating with a thickness of 90 μm, and then heat-treated at 200° C. for 20 min to melt and level, thereby obtaining an antibacterial powder coating.
[0068] Example 4
[0069] A polydopamine / nanosilver spherical antibacterial powder coating, the preparation method of which comprises the following steps:
[0070] (1) 127.5 g of polyamide PA powder and 22.5 g of fumed nano-silica 200 were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotary drum, and stirred for 120 s at an output power of 700 W; then, 600 mL of deionized water and 40% hydrofluoric acid solution were added and stirred for 12 h, wherein the molar ratio of HF to fumed nano-silica was 2:1; after the reaction was completed, 5 M NaOH solution was slowly added and the reaction was continued for 12 h, wherein the molar ratio of HF to NaOH was 1:2.5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain a spherical polyamide powder with a nanoporous structure.
[0071] (2) 50 g of the spherical polyamide powder with a nanoporous structure obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.75 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.4 with 0.25 M HCl; then 16.67 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a spherical polyamide powder functionalized with polydopamine.
[0072] (3) The polydopamine functionalized spherical polyamide powder was washed with deionized water under reduced pressure for three times and then placed in a 1000-mL beaker together with 400 mL of deionized water. A 2.5 g / L silver nitrate solution was slowly added and stirred at room temperature for 6.5 hours, wherein the mass ratio of the polydopamine functionalized spherical polyamide powder to AgNO3 was 9:2. Subsequently, NaBH4 was slowly added and heated and stirred at 50°C for 3 hours, wherein the molar ratio of AgNO3 to NaBH4 in the AgNO3 solution was 1:1. The powder was then washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0073] Furthermore, the polydopamine / nanosilver spherical antibacterial powder coating prepared above was electrostatically sprayed on a tinplate to form a coating with a thickness of 85 μm, and then heat-treated at 170° C. for 15 min to melt and level the coating, thereby obtaining an antibacterial powder coating.
[0074] Example 5
[0075] A polydopamine / nanosilver spherical antibacterial powder coating, the preparation method of which comprises the following steps:
[0076] (1) 133.33 g of a polyester resin / TGIC mixture (wherein the mass ratio of polyester resin to TGIC is 96:4) and 16.67 g of nano-alumina were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotary drum, and stirred for 120 s at an output power of 700 W; then, 600 mL of deionized water and 40% hydrochloric acid solution were added, stirred and reacted for 12 h, wherein the molar ratio of HCl to nano-alumina was 2:1; after the reaction was completed, 5 M NaOH solution was slowly added and continued to react for 12 h, wherein the molar ratio of HCl to NaOH was 1:2.5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain a spherical polyester TGIC powder with a nanoporous structure.
[0077] (2) 50 g of the spherical polyester TGIC powder with a nanoporous structure obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.8 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.6 with 0.5 M HCl; then 33.33 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a spherical polyester TGIC powder functionalized with polydopamine.
[0078] (3) The polydopamine functionalized spherical polyester TGIC powder was washed with deionized water under reduced pressure for three times and then placed in a 1000 mL beaker together with 400 mL of deionized water. 1 g / L of silver nitrate solution was slowly added and stirred at room temperature for 6 hours, wherein the mass ratio of the polydopamine functionalized spherical polyester TGIC powder to AgNO3 was 10:1; then DMF was slowly added and heated and stirred at 50°C for 3.5 hours, wherein the molar ratio of AgNO3 to DMF in the AgNO3 solution was 1:1; then the powder was washed with deionized water for 4 times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0079] Furthermore, the polydopamine / nanosilver spherical antibacterial powder coating prepared above was electrostatically sprayed on a tinplate to form a coating with a thickness of 90 μm, and then heat-treated at 170° C. for 5 min to achieve melt leveling, thereby obtaining an antibacterial powder coating.
[0080] Example 6
[0081] A polydopamine / nanosilver spherical antibacterial powder coating, the preparation method of which comprises the following steps:
[0082] (1) 131.25 g of polyurethane and 18.75 g of fumed nano-silica A200 were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotating drum, and stirred for 110 s at an output power of 700 W; then, 600 mL of deionized water and 40% dilute sulfuric acid solution were added and stirred for 12 h, wherein the molar ratio of H2SO4 to fumed nano-silica was 1:1; after the reaction was completed, 5 M NaOH solution was slowly added and the reaction was continued for 12 h, wherein the molar ratio of H2SO4 to NaOH was 1:5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain a spherical polyurethane powder with a nanoporous structure.
[0083] (2) 50 g of the spherical polyurethane powder with a nanoporous structure obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.85 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.7 with 0.75 M HCl; then 20 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a spherical polyurethane powder functionalized with polydopamine.
[0084] (3) The polydopamine functionalized spherical polyurethane powder was washed with deionized water under reduced pressure for three times and then placed in a 1000-mL beaker together with 400 mL of deionized water. 1 g / L silver nitrate solution was slowly added and stirred at room temperature for 5 hours, wherein the mass ratio of the polydopamine functionalized spherical polyurethane powder to AgNO3 was 7:1. Subsequently, glucose was slowly added and heated and stirred at 50°C for 4 hours, wherein the molar ratio of AgNO3 to glucose in the AgNO3 solution was 1:1. The powder was then washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0085] Furthermore, the polydopamine / nanosilver spherical antibacterial powder coating prepared above was electrostatically sprayed on a tinplate to form a coating with a thickness of 80 μm, and then heat-treated at 170° C. for 8 min to achieve melt leveling, thereby obtaining an antibacterial powder coating.
[0086] Example 7
[0087] A polydopamine / nanosilver spherical antibacterial powder coating, the preparation method of which comprises the following steps:
[0088] (1) 128.57 g of polyester resin / E12 mixture (wherein the mass ratio of polyester resin to E12 is 50:50) and 21.43 g of fumed nano-silica R972 were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotary drum, and stirred for 120 s at an output power of 700 W; then, 600 mL of deionized water and 40% hydrochloric acid solution were added and stirred for 12 h, wherein the molar ratio of HCl to fumed nano-silica was 4:1; after the reaction was completed, 5 M NaOH solution was slowly added and the reaction was continued for 12 h, wherein the molar ratio of HCl to NaOH was 1:2.5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain spherical polyester E12 powder with a nanoporous structure.
[0089] (2) 50 g of the spherical polyester E12 powder with a nanoporous structure obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.55 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.8 with 1 M HCl; then 75 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a polydopamine-functionalized spherical polyester E12 powder.
[0090] (3) The polydopamine functionalized spherical polyester E12 powder was washed with deionized water under reduced pressure for three times and then placed in a 1000 mL beaker together with 400 mL of deionized water. A 3 g / L silver nitrate solution was slowly added and stirred at room temperature for 5.5 hours, wherein the mass ratio of the polydopamine functionalized spherical polyester E12 powder to AgNO3 was 5:1; then ascorbic acid was slowly added and heated and stirred at 50°C for 4 hours, wherein the molar ratio of AgNO3 to ascorbic acid in the AgNO3 solution was 1:1; then the powder was washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0091] Furthermore, the polydopamine / nanosilver spherical antibacterial powder coating prepared above was electrostatically sprayed on a tinplate to form a coating with a thickness of 80 μm, and then heat-treated at 170° C. for 8 min to achieve melt leveling, thereby obtaining an antibacterial powder coating.
[0092] Example 8
[0093] A polydopamine / nanosilver spherical antibacterial powder coating, the preparation method of which comprises the following steps:
[0094] (1) 125 g of a polyester resin and E12 mixture (wherein the mass ratio of polyester resin to E12 is 50:50) and 25 g of nano-ferroferric oxide were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotary drum, and stirred for 130 s at an output power of 700 W; then, 600 mL of deionized water and 40% hydrofluoric acid solution were added and stirred for 12 h, wherein the molar ratio of HF to nano-ferroferric oxide was 4:1; after the reaction was completed, 5 M NaOH solution was slowly added and the reaction was continued for 12 h, wherein the molar ratio of HF to NaOH was 1:2.5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain spherical polyester E12 powder with a nanoporous structure.
[0095] (2) 50 g of the spherical polyester E12 powder with a nanoporous structure obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.5 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 9.0 with 0.25 M HCl; then 30 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a polydopamine-functionalized spherical polyester E12 powder.
[0096] (3) The polydopamine functionalized spherical polyester E12 powder was washed with deionized water under reduced pressure for three times and then placed in a 1000-mL beaker together with 400 mL of deionized water. 1.5 g / L of silver nitrate solution was slowly added and stirred at room temperature for 6.5 hours, wherein the mass ratio of the polydopamine functionalized spherical polyester E12 powder to AgNO3 was 8:0.5; then NaBH4 was slowly added and heated and stirred at 50°C for 4 hours, wherein the molar ratio of AgNO3 to NaBH4 in the AgNO3 solution was 1:1; then the powder was washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
[0097] Furthermore, the polydopamine / nanosilver spherical antibacterial powder coating prepared above was electrostatically sprayed on a tinplate to form a coating with a thickness of 80 μm, and then heat-treated at 170° C. for 15 min to melt and level, thereby obtaining an antibacterial powder coating.
[0098] Comparative Example 1
[0099] An antibacterial powder coating, the preparation method of which comprises the following steps:
[0100] (1) 120 g of polyamide PA powder and 30 g of fumed nano-silica R972 were mixed evenly using a wall breaker, placed in a microwave oven equipped with a rotary drum, and stirred for 110 s at an output power of 700 W; then, 600 mL of deionized water and 40% hydrofluoric acid solution were added and stirred for 12 h, wherein the molar ratio of HF to fumed nano-silica was 1.5:1; after the reaction was completed, 5 M NaOH solution was slowly added and the reaction was continued for 12 h, wherein the molar ratio of HF to NaOH was 1:2.5; after washing with deionized water 4 times, the mixture was placed in a vacuum oven at 40°C and dried for 48 h to obtain a spherical polyamide powder with a nanoporous structure.
[0101] (2) 50 g of the mixture obtained in step (1) and 400 mL of deionized water were placed in a 1000 mL beaker, and 2 g / L of silver nitrate solution was slowly added and stirred at room temperature for 6 hours, wherein the mass ratio of the mixture to AgNO3 was 8:1; then DMF was slowly added and heated and stirred at 50°C for 4 hours, wherein the molar ratio of AgNO3 to DMF was 1:1; then the mixture was washed with deionized water for 4 times, and dried in a vacuum oven at 40°C for 48 hours to obtain an antibacterial powder coating.
[0102] Furthermore, the antibacterial powder coating prepared above was applied to a tinplate plate by electrostatic spraying to form a coating with a thickness of 80 μm, and then heat-treated at 170° C. for 10 min to achieve melt leveling, thereby obtaining an antibacterial powder coating.
[0103] Comparative Example 2
[0104] An antibacterial powder coating, the preparation method of which comprises the following steps:
[0105] (1) 50 g of polyamide powder was placed in a 1000 mL beaker, 500 mL of deionized water and 0.6 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.4 with 0.5 M HCl; then 25 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain polydopamine functionalized polyamide powder.
[0106] (2) The polydopamine functionalized polyamide powder was washed with deionized water under reduced pressure for three times and then placed in a 1000-mL beaker together with 400 mL of deionized water. A 2 g / L silver nitrate solution was slowly added and stirred at room temperature for 5 hours, wherein the mass ratio of the polydopamine functionalized polyamide powder to AgNO3 was 8:1. Subsequently, DMF was slowly added and heated and stirred at 50°C for 5 hours, wherein the molar ratio of AgNO3 to DMF in the AgNO3 solution was 1:1. The powder was then washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain an antibacterial powder coating.
[0107] Furthermore, the antibacterial powder coating prepared above was applied to a tinplate plate by electrostatic spraying to form a coating with a thickness of 80 μm, and then heat-treated at 170° C. for 15 min to achieve melt leveling, thereby obtaining an antibacterial powder coating.
[0108] Comparative Example 3
[0109] An antibacterial powder coating, the preparation method of which comprises the following steps:
[0110] (1) 120 g of polyamide PA powder and 30 g of fumed nano-silica R972 were mixed evenly using a wall breaking machine, placed in a microwave oven equipped with a rotary drum, and stirred for 110 s at an output power of 700 W; washed with deionized water for 4 times and then placed in a 40° C. vacuum oven for 48 h to obtain polyamide powder.
[0111] (2) 50 g of the polyamide powder obtained in step (1) was placed in a 1000 mL beaker, 500 mL of deionized water and 0.6 g of tris(hydroxymethyl)aminomethane were added, and the pH was adjusted to 8.2 with 0.5 M HCl; then 25 g of dopamine hydrochloride was added and stirred at room temperature for 24 h to obtain a polydopamine functionalized polyamide powder.
[0112] (3) The polydopamine functionalized polyamide powder was washed with deionized water under reduced pressure for three times and then placed in a 1000-mL beaker with 400 mL of deionized water. A 2 g / L silver nitrate solution was slowly added and stirred at room temperature for 6 hours, wherein the mass ratio of the polydopamine functionalized polyamide powder to AgNO3 was 8:1. Subsequently, DMF was slowly added and heated and stirred at 50°C for 4 hours, wherein the molar ratio of AgNO3 to DMF in the AgNO3 solution was 1:1. The powder was then washed with deionized water for four times and dried in a vacuum oven at 40°C for 48 hours to obtain a polydopamine / nanosilver antibacterial powder coating.
[0113] Furthermore, the polydopamine / nanosilver antibacterial powder coating prepared above was applied to a tinplate plate by electrostatic spraying to form a coating with a thickness of 100 μm, and then heat-treated at 170° C. for 10 min to achieve melt leveling, thereby obtaining an antibacterial powder coating.
[0114] Comparative Example 4
[0115] The polyamide PA powder was electrostatically sprayed on the tinplate to form a coating with a thickness of 80 μm, and then heat-treated at 170° C. for 15 minutes to melt and level the tinplate, thereby obtaining a PA powder coating.
[0116] Verification Example 1
[0117] The polyamide powder obtained before and after treatment with the barrier agent and the etchant in step (1) of Example 1 was respectively taken, and its morphology was detected by scanning electron microscopy. The results are as follows: Figure 2 As shown. Figure 2 (a) and Figure 2 (c) is untreated polyamide raw powder, Figure 2 (b) and Figure 2 (d) is the spherical polyamide powder with nanoporous structure obtained after treatment. The results show that after the polyamide powder is treated with the barrier agent, the spherical change of its surface is obvious. After sphericalization, it is further treated with an etchant to remove the barrier material, so that a porous structure is formed on the surface of the polyamide, which is conducive to the subsequent loading of silver. The spherical antibacterial powder coating prepared in Example 1 was tested using an X-ray diffractometer. The results are as follows: Figure 3 The results show that the desired content of silver component is successfully loaded into the obtained antibacterial powder coating.
[0118] Subsequently, the powder coatings prepared in Examples 1-8 and Comparative Examples 1-4 were respectively taken to test their repose angle, collapse angle, difference angle and flow index and the antibacterial rate of the prepared panels. The test results are shown in Table 1 and Figure 4 shown.
[0119] Table 1 Performance data of antibacterial powder coatings of Examples 1-8 and Comparative Examples 1-4
[0120] sample Angle of repose Crash Angle Difference Angle Flow Index Antimicrobial Example 1 35° 18.9° 16.1° 131.8 99.9% Example 2 34.6° 18.8° 15.8° 138.9 98.6% Example 3 34.4° 18.9° 15.5° 141.2 95.7% Example 4 37.3° 21.1° 16.2° 129.3 98.9% Example 5 41.5° 21.1° 20.4° 98.6 96.3% Example 6 39.7° 20.9° 18.8° 103.7 99.7% Example 7 38.7° 21.5° 17.2° 112.8 95.82% Example 8 37.4° 20.6° 16.8° 119.7 97.38% Comparative Example 1 38.3° 21.4° 16.9° 116.6 80.70% Comparative Example 2 44.5° 21.2° 23.3° 67.74 91.67% Comparative Example 3 32.5° 18.6° 13.9° 149.8 \ Comparative Example 4 42.9° 20.8° 22.1° 73.96 \
[0121] The spheroidization preparation process and mechanism of the polydopamine nanosilver spherical antibacterial powder coating of the present invention can be found in Figure 1 When the surface tension of a fluid is significantly higher than gravity or other forces, the fluid will take on a spherical shape. In the absence of other forces, surface tension will minimize the surface of a given volume, making the droplets spherical. A spherical powder coating is obtained by using the surface tension of molten droplets or solution droplets to transform irregularly shaped powder coating particles into spherical particles. In order to reduce the stacking of powders during the spheroidization process, a barrier agent is added for dispersion. The barrier agent itself is a flow aid. The more it is added, the better the fluidity of the powder itself. Since the amount of the barrier agent added is more than 15%, and the amount of powder coating nanoparticles added should not exceed 0.8%, if it exceeds 0.8%, the more it is added, the coating will have many pinholes, shrinkage holes, and pores. In severe cases, the coating film cannot be formed and the leveling of the coating decreases, so an etchant is needed to remove the barrier agent. Although polydopamine was added to Comparative Example 2, the powder was not spheroidized, so the surface leveling was obviously not as good as that of Example 1 of the present invention, and many cracks appeared on the surface of the formed film; although the powder was spheroidized by a barrier agent in Comparative Example 3, the barrier agent was not further treated with an etchant. Although the fluidity was the best, the proportion of the barrier agent far exceeded the requirements of the powder coating, making it difficult for the final product to form a film and it would fall apart at the touch, so the subsequent antibacterial test of the board surface could not be carried out; Comparative Example 4 used polyamide powder without any treatment, which also had the problem of poor leveling, and many bubbles appeared on the surface of the formed film. It can be seen that spheroidizing the powder with a barrier agent and removing the barrier agent are key factors in improving the leveling and film formation of the coating.
[0122] The antibacterial tests in the chart all used Escherichia coli liquid, which was cultured on the coating for 6 hours and then diluted 10 times, 100 times, 1000 times, and 10,000 times respectively, and then applied on the culture medium. Comparative Example 4 was used as a blank control group, and the antibacterial rate was calculated based on the difference in colony counts. Subsequently, the antibacterial coating synthesized in Example 1 and the pure polyamide powder coating synthesized in Comparative Example 4 were taken for antibacterial testing. Specifically, this test used Escherichia coli liquid, which was cultured on the coating for 1 hour and 6 hours and then diluted 10 times, 100 times, 1000 times, and 10,000 times respectively, and then applied on the culture medium. The results are shown in Figure 2. Figure 5 As shown, Figure 5 (a) and Figure 5 (c) is a graph showing the number of colonies on the plate of the coating of Comparative Example 4 at the corresponding dilution multiples after 1 hour and 6 hours of bacterial culture; Figure 5 (b) and Figure 5(d) is a graph of the number of plate colonies of the coating prepared by AgNPs@PDA@PA in Example 1 at the corresponding dilution multiples after 1h and 6h of bacterial culture. The results show that the coating component of Comparative Example 4 is only polyamide PA powder, which is used as a blank control group without any treatment. Therefore, the antibacterial rate of the antibacterial coating of Example 1 after 1h of culture is 36.95%, and the antibacterial effect of the coating after 6h of culture is 99.9%. With the passage of time, the antibacterial effect is significantly improved, reflecting the synergistic antibacterial effect after loading Ag.
[0123] Since the board surface leveling performance in Comparative Examples 2 and 3 is poor, especially in Comparative Example 3, even film formation is impossible, the subsequent antibacterial test of the board surface cannot be carried out. Therefore, Example 1 and Comparative Example 1 are further used for antibacterial performance comparison (Escherichia coli liquid is cultured on the coating for 6 hours), and Comparative Example 4 is used as a blank control. The results are as follows Figure 6 As shown. The results show that the antibacterial rate of Example 1 is significantly improved compared with that of Comparative Example 1; since polydopamine is not used as a carrier in Comparative Example 1, under the condition of the same amount of Ag added, its antibacterial performance is not as good as that of polydopamine. The main reason is that since polydopamine has effective loading sites for silver ions, it can effectively disperse silver ions. Directly adding nanosilver reduces the utilization rate of silver ions due to the easy agglomeration of nano-scale materials. In contrast, the role of polydopamine is reflected; in Comparative Example 2, the powder is not spheroidized, and the fluidity of the powder is far inferior to that of other spheroidized powder particles, and the leveling of the final board surface is also inferior to that of the spheroidized powder coating.
[0124] The above specific implementation method part specifically introduces the technical solutions involved in the present invention. It should be noted that the above introduction is only to help those skilled in the art better understand the methods and ideas of the present invention, rather than limiting the relevant contents. Without departing from the principles of the present invention, those skilled in the art may also make appropriate adjustments or modifications to the present invention, and the above adjustments and modifications shall also fall within the scope of protection of the present invention.
Claims
1. A method for preparing a polydopamine / nanosilver spherical antibacterial powder coating, characterized in that: The steps include: (1) The resin powder coating matrix and the barrier agent are mixed evenly and placed in a microwave oven, and stirred at an output power of 500-1000 W; then, water and an etchant are added and stirred for 6-24 hours; after the reaction is completed, an alkaline solution is added and the reaction is continued for 6-24 hours, and then washed and dried to obtain a spherical resin powder with a nanoporous structure; (2) placing the spherical resin powder with a nanoporous structure obtained in step (1) in a container, adding water and tris(hydroxymethyl)aminomethane, and adjusting the pH to 8-9 using a pH adjuster; then adding dopamine hydrochloride and stirring to react to obtain a polydopamine functionalized spherical powder; (3) The polydopamine functionalized spherical powder is washed and placed in a container together with water, and a silver nitrate solution is slowly added for stirring reaction; then a reducing agent is slowly added for heating and stirring reaction, and then washed and dried to obtain a polydopamine / nanosilver spherical antibacterial powder coating.
2. The preparation method according to claim 1, characterized in that: The resin powder coating matrix in step (1) is selected from one or more of triglycidyl isocyanurate, polyester resin, epoxy resin E12, polyurethane resin, polyamide resin, polyethylene resin, and fluorocarbon resin.
3. The preparation method according to claim 1, characterized in that: The barrier agent in step (1) is selected from one or more of fumed nano-silicon dioxide, fumed nano-silicon dioxide, nano-zinc oxide, nano-ferroferric oxide, and nano-aluminum oxide.
4. The preparation method according to claim 1, characterized in that: The etchant in step (1) is selected from one or more of HCl, HF, LiF, and H2SO4.
5. The preparation method according to claim 1, characterized in that: In step (1), the output power of the microwave oven is 600-900W, and the stirring time is 80-150s.
6. The preparation method according to claim 1, characterized in that: The stirring reaction in step (2) is carried out at a temperature of 18-30° C. and for a time of 12-48 hours.
7. The preparation method according to claim 1, characterized in that: The reducing agent in step (3) is selected from one or more of DMF, glucose, ascorbic acid, and NaBH4.
8. The preparation method according to claim 1, characterized in that: The temperature of the heating and stirring reaction in step (3) is 40-60° C. and the time is 1-7 h.
9. The polydopamine / nanosilver spherical antibacterial powder coating prepared according to the preparation method according to any one of claims 1 to 8.
10. An antibacterial powder coating, characterized in that: The invention comprises a polydopamine / nanosilver spherical antibacterial powder coating prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Preparation method of quaternary ammonium salt polymer antibacterial agent and silver-loaded compound antibacterial agent thereof on basis of ATRP method
CN105801734A
Production method of medical polyurethane antibacterial nano-silver coating
CN107583112A
Preparation method of carbon-silver microsphere / epoxy resin super-hydrophobic coating
CN108774447A
Antibacterial powder coating suitable for metal coiled material and preparation method of antibacterial powder coating
CN117165148A